TELAAH RINGKAS KITAB FASL AL-MAQĀL OLEH IBN RUSHD - ahmad nabil amir; Tasnim Abdul Rahman (LPPM STAI Nida El-Adabi, 2025)
The paper aims to study the influence of Islam in world history by taking a preliminary analysis of kitab Fasl al-maqal by Ibn Rushd. It analyses the ideas and influence of Abu’l-Walid Muhammad ibn Ahmad ibn Rushd (1126-1198) in inspiring the Age of Enlightenment in Europe. His philosophical works and doctrine written in early 6-12th centuries has manifested dramatic influence in the making of Western civilization as recognized in the late 18th century renaissance. The phenomenal impact of this highly Muslim contribution was seen in the cultural worldview that constitute the cornerstone of Western Europe. The study is based on qualitative approaches in the form of literature review and content analysis. The data were obtained from primary and secondary sources and analyzed by way of descriptive, analytical, thematic, hermeneutic, synthetic and historical technique. The finding shows that the works and thought of Ibn Rushd as presented in Fasl al-Maqal (The Decisive Treatise) has inspired radical intellectual transformation in European society. This paper contributes to highlight historical influence of his scientific works that constitute the cornerstone of his worldview and discuss the monumental socio-religious reform initiated by this great giant, Ibn Rushd representing the political landscape of al-Andalus and the history of Western Europe.